Myxomycete research in the XXI Century - Rojas, Carlos; Kryvomaz, Tetyana (My University, 2017)
Myxomycetes: Biology, Systematics, Biogeography, and Ecology is a comprehensive overview of the body of accumulated knowledge that now exists on myxomycetes. Its broad scope takes an integrated approach to the knowledge of this organismal group, considering a number of important aspects of their genetics and molecular phylogeny. It also treats myxomycetes as a distinct group from fungi, and includes molecular information that discusses the systematics and evolutionary pathways of the group. Additionally, biomedical and engineering applicability is discussed, thus expanding the audience and use of the book in a multidisciplinary context. The book provides an authoritative resource for students, researchers and educators interested in the fields of protistology, microbial ecology, molecular microbiology, biogeography, mycology, biodiversity, and evolutionary biology, and will also interest the amateur naturalist and biologist.
Keywords: myxomycetes; systematics; ecology